2021
DOI: 10.1177/0271678x211028496
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of leukocyte populations in intracranial blood collected during mechanical thrombectomy

Abstract: Using standard techniques during mechanical thrombectomy, the Blood and Clot Thrombectomy Registry and Collaboration (BACTRAC) protocol (NCT03153683) isolates intracranial arterial blood distal to the thrombus and proximal systemic blood in the carotid artery. We augmented the current protocol to study leukocyte subpopulations both distal and proximal to the thrombus during human stroke (n = 16 patients), and from patients with cerebrovascular disease (CVD) undergoing angiography for unrelated conditions (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…To date, the recent study of Shaw and colleagues and our present work are the first studies using flow-cytometry to analyze leukocyte subpopulations in ischemic blood samples locally aspirated during MT. 5 While leukocyte isolation and cryopreservation led to a significant cellular loss within the granulocyte population in the study by Shaw et al., we could show by automatic cell counting that the absolute numbers of granulocytes increased within the secluded ischemic vasculature and made up the predominant leukocyte population, confirming our previous results from two independent prospective cohorts, which were based on manual cell counting. 2 , 4 In line with the data of Shaw and colleagues, we detected a shift within the lymphocyte population towards higher percentages of T cells in the ischemic compartment compared to systemic blood samples.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…To date, the recent study of Shaw and colleagues and our present work are the first studies using flow-cytometry to analyze leukocyte subpopulations in ischemic blood samples locally aspirated during MT. 5 While leukocyte isolation and cryopreservation led to a significant cellular loss within the granulocyte population in the study by Shaw et al., we could show by automatic cell counting that the absolute numbers of granulocytes increased within the secluded ischemic vasculature and made up the predominant leukocyte population, confirming our previous results from two independent prospective cohorts, which were based on manual cell counting. 2 , 4 In line with the data of Shaw and colleagues, we detected a shift within the lymphocyte population towards higher percentages of T cells in the ischemic compartment compared to systemic blood samples.…”
supporting
confidence: 90%
“…Their analysis uncovered differences in lymphocyte subsets within the intracranial arterial blood compared to the systemic circulation, but the observed granulocyte fraction was exceedingly low. 5 We here report on a shift in leukocyte subsets sampled directly from the secluded cerebral vasculature before MT. In this cohort of 36 stroke patients, we performed immediate flow-cytometry analysis of these whole blood samples conserving all leukocyte subpopulations.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Thus far, we were able to prospectively and consecutively observe the two largest independent cohorts (n = 318 in this study, n = 183 previously reported [17]) in which immune cells of AIS patients (n = 58 in this study, n = 40 previously reported [17]) could be harvested from the occluded cerebral vascular compartment and analyzed with a high degree of standardization [34]. As a main finding of the current study, local immune cell infiltration into the occluded cerebral vascular compartment could be reproduced with very similar qualitative and quantitative observations in comparison to previous observations [17].…”
Section: Discussionmentioning
confidence: 99%